Vaccatides: Antifungal Glutamine-Rich Hevein-Like Peptides from Vaccaria hispanica - Wong, Ka H.; Tan, Wei Liang; Kini, Shruthi G.; Xiao, Tianshu; Serra, Aida; Sze, Sui Kwan; Tam, James P. (Frontiers in Plant Science, 2017)
Hevein and hevein-like peptides are disulfide-constrained chitin-binding cysteine-rich peptides. They are divided into three subfamilies, 6C-, 8C- and 10C-hevein-like peptides, based on the number of cysteine residues. In addition, hevein-like peptides can exist in two forms, short and long. The long C-terminal form found in hevein and 10C-hevein-like peptides contain a C-terminal protein cargo. In contrast, the short form without a protein cargo is found in all three subfamilies. Here, we report the discovery and characterization of two novel glutamine-rich and protein cargo-free 8C-hevein-like peptides, vaccatides vH1 and vH2, from Vaccaria hispanica of the Caryophyllaceae family. Proteomic analyses showed that the vaccatides are 40‒41 amino acids in length and contain a chitin-binding domain. NMR determination revealed that vaccatide vH2 displays a highly compact structure with a cystine knot at the N-terminus and an additional disulfide bond at the C-terminus. Stability studies showed that this compact structure renders vaccatide vH2 resistant to thermal, chemical and proteolytic degradation. The chitin-binding vH2 was shown to inhibit the mycelium growth of four phyto-pathogenic fungal strains with IC50 values in the micromolar range. Our findings show that vaccatides represent a new family of 8C-hevein-like peptides, which are protein cargo-free and glutamine-rich, characteristics that differentiate them from the prototypic hevein and the 10C-hevein-like peptides.Together, this study expands the existing library of hevein-like peptides and provides insight into their molecular diversity in sequence, structure and biosynthesis. Additionally, their highly disulfide-constrained structure could be used as a scaffold for developing metabolically and orally active peptidyl therapeutics.